Significance of motivational interviewing in public health - Szczekala, Katarzyna; Kanadys, Katarzyna; Wiktor, Krzysztof; Wiktor , Henryk (Polish Journal of Public Health, 2019)
Motivational interviewing (MI) is a specific style of communication based on collaboration, aimed at achieving a goal and focused on change talk. This is conducted in an atmosphere of comprehension, acceptance and compassion, being intended to strengthen inner motivation and commitment to attain goals by the search for, and assessment of, the individual’s reasons for change. Change talk may refer to new behaviours, lifestyles or the introduction of treatment adherence. Therefore, it can be a part of health care provider – patient communication. The application of MI contributes to an increase in patients’ concordance and compliance as well as rightness of the therapy prescribed because it heightens an individual’s awareness and eagerness to change and triggers positive thinking, being focused on resources and values. The aim of this article is to familiarise the MI character and present some interesting examples characterised by a diversity of ideas in the overall vision of public health concentrated on health promotion. A non-systematic literature review of the years 2003-2018 on the use of MI in health promotion in PubMed provided evidence of great interest in MI in such contexts as body weight reduction, an increase in physical activity, or coping with risk behaviours e.g. addictions. The aforementioned problems are a major cause of non-communicable diseases. The application of MI results in health behaviour improvement along with increased self-esteem and self-efficacy, inner motivation and willingness to change habits